Зменшення непродуктивних теплових втрат при генерації енергії - Демченко, Володимир Георгійович; Коник, Аліна Василівна (Національний технічний університет "Харківський політехнічний інститут", 2020)
Стаття присвячена аналізу непродуктивних втрат при генерації теплової енергії. Встановлено причини теплових втрат на станційному обладнанні, технологічному трубопроводі та при розбалансуванні технологічних процесів. В результаті надані рекомендації сумісного застосування атомних електростанцій (АЕС) або теплових електростанцій (ТЕС) з доступними відновлюваними джерелами енергії (ВДЕ), за допомогою систем теплового акумулювання, що дасть можливість збалансувати систему «генерація – транспортування – споживання». Застосування стаціонарних та мобільних теплових акумуляторів при генерації дозволить знизити теплові втрати.

The article is devoted to the analysis of non-productive losses in the generation of thermal energy. The causes of heat losses and their localization on the station equipment, technological pipeline and at unbalance of technological processes are established. As a result of the analysis, recommendations were given for the joint use of nuclear power plants (NPPs) or thermal power plants (TPPs) with available renewable energy sources (RES), using thermal storage systems, which will balance the system "generation - transportation - consumption". The use of stationary and mobile heat accumulators in the generation of RES, secondary thermal energy (TER) will reduce heat loss, use low-potential sources, which will relieve service equipment, reduce fuel consumption (FER) and harmful emissions into the environment. Also, it is recommended to conduct a full energy audit of station equipment and pipelines. Implement replacement of technically obsolete equipment with low efficiency, replace piping and insulation. Update the automation system, introduce a process scheduling system. Balance technological processes.
Reducing of non-productive heat losses in energy generation
Keywords: тепловий акумулятор; heat storage